Perhitungan Harga Pokok Produksi dengan Menggunakan Metode Harga Pokok Pesanan-Full Costing pada Anisa Catering Jepara - Ainiah, Siti Mahmubatun; Primastiwi, Anita (EQUILIBRIUM - Jurnal Bisnis dan Akuntansi, 2024)
This research aims to evaluate Paket Ayam Bakar (Grilled Chicken Packages) costs of goods manufactured at Anisa Catering. This research is descriptive based on quantitative data. Primary and secondary data were obtained through interviews, observation and documentation. The evaluation was done by calculation comparition of the Paket Ayam Bakar production cost, calculation by Anisa Catering has differences with the calculation carried out using full costing approach. Research results show that there is a difference in job order costing calculation according to Anisa Catering and the calculation according to theory. Anisa Catering calculation shows the result was greater at IDR 4,503. This difference occurred because Anisa Catering had calculating raw material costs and direct labor costs greater than it should, the company had not yet included account electricity costs, fuel costs, gas costs, land and building tax costs, and asset depreciation costs into factory overhead costs. The impact of this practice shows that Anisa Catering set selling price too high, so that it cannot compete with Paket Ayam Bakar from other companies. The occurrence of this error shows that it is still necessary to improve the calculation of orders cost at Anisa Catering, and that assistance from competent parties will help to improve the determination orders cost at Anisa Catering so that it suitable with job order costing theory using full costing approach.